A Rhodococcal Transcriptional Regulatory Mechanism Detects the Common Lactone Ring of AHL Quorum-Sensing Signals and Triggers the Quorum-Quenching Response - Barbey, Corinne; Chane, Andrea; Burini, Jean-François; Maillot, Olivier; Merieau, Annabelle; Gallique, Mathias; Beury-Cirou, Amélie; Konto-Ghiorghi, Yoan; Feuilloley, Marc; Gobert, Virginie; Latour, Xavier (Frontiers in Microbiology, 2018)
The biocontrol agent Rhodococcus erythropolis disrupts virulence of plant and human Gram-negative pathogens by catabolizing their N-acyl-homoserine lactones. This quorum-quenching activity requires the expression of the qsd (quorum-sensing signal degradation) operon, which encodes the lactonase QsdA and the fatty acyl-CoA ligase QsdC, involved in the catabolism of lactone ring and acyl chain moieties of signaling molecules, respectively. Here, we demonstrate the regulation of qsd operon expression by a TetR-like family repressor, QsdR. This repression was lifted by adding the pathogen quorum signal or by deleting the qsdR gene, resulting in enhanced lactone degrading activity. Using interactomic approaches and transcriptional fusion strategy, the qsd operon derepression was elucidated: it is operated by the binding of the common part of signaling molecules, the homoserine lactone ring, to the effector-receiving domain of QsdR, preventing a physical binding of QsdR to the qsd promoter region. To our knowledge, this is the first evidence revealing quorum signals as inducers of the suitable quorum-quenching pathway, confirming this TetR-like protein as a lactone sensor. This regulatory mechanism designates the qsd operon as encoding a global disrupting pathway for degrading a wide range of signal substrates, allowing a broad spectrum anti-virulence activity mediated by the rhodococcal biocontrol agent. Understanding the regulation mechanisms of qsd operon expression led also to the development of biosensors useful to monitor in situ the presence of exogenous signals and quorum-quenching activity.